Scary stories 3 : more tales to chill your bones - Schwartz, Alvin, 1927-1992 (Harper, an imprint of HarperCollinsPublishers, 2017)
Features twenty-five chilling tales of prophetic dreams, feral children raised by wild animals, swamp creatures, and other terrifying phenomena.